2014
DOI: 10.1016/j.adengl.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Our Experience With Wet-Wrap Treatment

Abstract: A wide range of treatments are currently available for severe atopic dermatitis, including systemic therapies such as ciclosporin, corticosteroids, azathioprine, methotrexate, mofetil mycophenolate, and omalizumab. In patients who can no longer take systemic drugs or who need a dose reduction, wet-wrap treatment can be an excellent option. To date, wet wraps have mostly been used in severe cases of childhood atopic dermatitis. We report our experience with wet-wrap treatment in 5 adults with atopic dermatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Reviewing the literature on side effects in WWT leads to a division into 3 categories (Table II): expected discomforts regarding the use of moist bandages (8,10,23,36), skin infections and probably the most serious adverse effect: possible systemic bioactivity of the TCS. Infections.…”
Section: What Are Potential Adverse Effects?mentioning
confidence: 99%
“…Reviewing the literature on side effects in WWT leads to a division into 3 categories (Table II): expected discomforts regarding the use of moist bandages (8,10,23,36), skin infections and probably the most serious adverse effect: possible systemic bioactivity of the TCS. Infections.…”
Section: What Are Potential Adverse Effects?mentioning
confidence: 99%
“…Wet-wrap therapy (WWT) can be helpful to quickly reduce AD severity, and it is often useful for acute flares and/or recalcitrant disease 88 89 90 91 92 93 94 95 96 97 . For better results and to reduce the risk of infection, WWT use must be based on proper education and can be administered on an outpatient or inpatient basis 88 94 .…”
Section: Resultsmentioning
confidence: 99%
“…3,4 WWT is an interesting alternative for short-term control in patients with severe or refractory flares that avoids the use of systemic and potentially more toxic treatments. 3,4 Its efficacy has been claimed to derive from better penetration of the steroid, decrease in transepidermal water loss, or from the wraps acting as a barrier against scratching. 3 Several studies and qualitative reviews on WWT have reported promising results in the management of AD, although the number of patients included has been small.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Wet wrap therapy (WWT) involves the application of a topical steroid, diluted or not, under two layers of cotton bandages or garments: a wet inner layer and a dry outer layer. Wraps are left for 8–24 h per day, and treatment duration should not exceed 14 days . WWT is an interesting alternative for short‐term control in patients with severe or refractory flares that avoids the use of systemic and potentially more toxic treatments .…”
mentioning
confidence: 99%
See 1 more Smart Citation